2001
DOI: 10.1152/ajpregu.2001.280.5.r1510
|View full text |Cite
|
Sign up to set email alerts
|

Evidence supporting a physiological role for proANP-(1–30) in the regulation of renal excretion

Abstract: The experiments, performed in pentobarbital sodium-anesthetized rats, consisted of a 1-h equilibration period followed by two 30-min control periods. Subsequently, synthetic rat pro atrial natriuretic peptide (ANP) [proANP-(1-30)] (n = 8) was given as a bolus of 10 microg in 1 ml of 0.9% saline followed by an infusion at 30 ng/min (20 microl/min) for six additional periods. Control rats (n = 6) received only 0.45% saline in the appropriate volumes. Mean arterial pressure, renal blood flow, and glomerular filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 28 publications
5
53
0
Order By: Relevance
“…1). The main physiological properties of these four peptide hormones after their release from the heart are blood pressure regulation and the maintenance of plasma volume in animals (Vesely et al 1987, Martin et al 1990, Gunning et al 1992, Benjamin & Peterson 1995, Zeidel 1995, Villarreal et al 1999, Dietz et al 2001 and humans (Vesely et al 1994a(Vesely et al ,b, 1998. The cardiac hormones, synthesized in the atrium of the heart, are long-acting natriuretic peptide (LANP) that consists of the first 30 a.a. from the N-terminal end of the ANP prohormone; vessel dilator, a.a. 31-67; kaliuretic peptide, a.a. 79-98; and ANP, a.a. 99-126 of the 126 a.a. prohormone (Vesely 1992(Vesely , 2002; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1). The main physiological properties of these four peptide hormones after their release from the heart are blood pressure regulation and the maintenance of plasma volume in animals (Vesely et al 1987, Martin et al 1990, Gunning et al 1992, Benjamin & Peterson 1995, Zeidel 1995, Villarreal et al 1999, Dietz et al 2001 and humans (Vesely et al 1994a(Vesely et al ,b, 1998. The cardiac hormones, synthesized in the atrium of the heart, are long-acting natriuretic peptide (LANP) that consists of the first 30 a.a. from the N-terminal end of the ANP prohormone; vessel dilator, a.a. 31-67; kaliuretic peptide, a.a. 79-98; and ANP, a.a. 99-126 of the 126 a.a. prohormone (Vesely 1992(Vesely , 2002; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1). Within the 126 a.a. prohormone in the heart are four peptide hormones whose main biologic properties are blood pressure regulation and maintenance of plasma volume in animals [5][6][7][8][9][10][11] and humans [12][13][14][15][16]. These peptide hormones, numbered by their a.a. sequences beginning at the N-terminal end of the ANP prohormone, consist of the first 30 a.a. of the prohormone-that is, long acting natriuretic peptide (LANP), vessel dilator (a.a. 31-67), kaliuretic peptide (a.a. 79-98), and ANP (a.a. 99-126) [2,3].…”
Section: Cardiac Natriuretic Peptidesmentioning
confidence: 99%
“…Secretion rates calculated from the pro-ANP-(1-30) RIA (3)(4)(5) were used in all NRVM experiments as an index of cardiac hormone secretion. This assay measures the NH 2-terminus of the pro-ANP molecule, and we have shown that in both plasma and in our atrial tissue perfusates the peptide measured by this NH 2-terminal assay is consistent with pro-ANP-(1-30) (3,10).…”
Section: Measurement Of Pro-anp-(1-30) Secretion From Cultured Nrvmmentioning
confidence: 99%
“…The cultured cells were pretreated with the agonists/antagonists for 5 min before exposure to ET-1. Medium was collected at defined incubation times, centrifuged, and assayed for ANP and pro-ANP-(1-30) by RIA using methods previously described by our laboratory (4,5). The data are expressed as picograms of ANP or pro-ANP-(1-30) per tissue culture well or as ANP secretion rate in picograms per minute for atrial perfusates.…”
Section: Measurement Of Pro-anp-(1-30) Secretion From Cultured Nrvmmentioning
confidence: 99%
See 1 more Smart Citation